Habitat use, size structure and sex ratio of the spot-legged turtle, Rhinoclemmys punctularia punctularia (Testudines: Geoemydidae), in Algodoal-Maiandeua Island, Pará, Brazil. - Wariss, Manoela (2012)
Rhinoclemmys punctularia punctularia is a semi-aquatic chelonian found in Northern South America. We analyzed the habitat use, size structure and sex ratio of the species on Algodoal-Maiandeua Island, a protected area on the Northeastern coast of the Brazilian state of Pará. Four distinct habitats (coastal plain lake, flooded forest ?igapó?, interdunal lakes, and tidal channels) were surveyed during the rainy (March and April) and dry (August and September) seasons of 2009, using hoop traps. For the analysis of population structure, additional data were taken in March and August, 2008. A total of 169 individuals were captured in flooded forest (igapó), lakes of the coastal plain and, occasionally, in temporary pools. Capture rates were highest in the coastal plain lake, possibly due to the greater availability of the fruits that form part of the diet of R. p. punctularia. Of the physical-chemical variables measured, salinity appeared to be the only factor to have a significant negative effect on capture rates. The sex ratio was only slightly biased to females, and did not vary between habitats or seasons. Straight carapace length was significantly larger in females, but did not vary between habitats. Overall, the evidence indicates that both biotic and abiotic factors like food availability, low current and salinity, influence the habitats selection and use by R. p. punctularia on Algodoal-Maiandeua Island